Advancing gender equality through sustainability systems: Toolkit and good practices - Morgan, Miranda; Elias, Marlene; Bressand, Amandine; Stoikova, Anny (2024)
Sustainability systems (such as voluntary sustainability standard and certification schemes) are increasing their efforts to advance gender equality, recognising its importance both as a fundamental human right and as a means to achieving other aspects of sustainability. This toolkit aims to support these systems to advance their thinking and action on gender equality by compiling curated resources and practical case studies. The toolkit is structured around three levels on which they can tackle gender equality: at the organisational level; within standards and certifications; and through programmatic work. The toolkit also addresses data-related considerations needed to make progress on gender equality within and through sustainability systems.